Unconventional use of injectable long-acting cabotegravir and rilpivirine against HIV-1 in PWH in clinical need: 52 weeks real-world data - Valentina Iannone; Roberto Rossotti; Nicholas Brian Bana; Gabriele Cavazza; Federico D’Amico; Francesca Lombardi; Pierluigi Francesco Salvo; Gianmaria Baldin; Simona Di Giambenedetto; Dario Bernacchia; Gabriele Pagani; Alberto Borghetti; et al. (BMC Infectious Diseases)
Abstract Background Long-acting Cabotegravir and Rilpivirine (LA CAB + RPV) shows potential advantages in heavily comorbid and even in viremic people with HIV (PWH). We assessed LA CAB + RPV durability in a cohort of PWH with a high comorbidity burden and adherence issues. Methods Retrospective observational study in two Italian outpatient settings enrolling PWH who switched to LA CAB + RPV from February 2021 to January 2024 in presence of exclusion criteria enlisted in registrational trials or with other worrisome clinical risks. Kaplan-Meier (KM) was used to assess the probability of CAB/RPV discontinuation. Cox regression analysis was used to evaluate potential predictors of discontinuation. Results We enrolled 74 PWH, with a median of 7 injections (IQR 5–9), a median age of 53 years (IQR 45–61), median time of exposure to antiretrovirals of 11 years (IQR 8–18) and median time from HIV diagnosis of 11.8 years (IQR 6.6–18.2). Eleven (14.9%) discontinued LA CAB + RPV mainly for injection-site pain. Of 53 PWH who were undetectable before switch, 37 maintained viral suppression at week 52. We registered only one virological failure at week 12. Twenty-one started injections with unsuppressed viral loads (median 66 cps/ml, IQR 40–215) and 10 (47.6%) achieved viral suppression. Overall probability of discontinuation was 14.9% at week 52. Younger age was protective against discontinuation (HR 0.93, 95%CI 0.88–0.99, p = 0.048). Conclusions Our results support the potential advantages in using LA CAB + RPV in PWH with adherence issues and comorbidities.